Delayed Periorbital Abscess after Silicone Implant to Orbital Floor Fracture. Issue 2 (June 2016) - Dedhia, Raj; Tollefson, Travis T.
There is a lack of consensus regarding preferred implant materials for orbital floor fracture reconstruction, leading to surgeon- and institution-dependent preferences. A variety of implants are used for orbital floor fracture reconstruction, each with their own complication profile. Knowledge of different implant materials is critical to identifying complications when they present. We report a delayed periorbital abscess 5 years after orbital floor reconstruction using a silicone implant.